2012
DOI: 10.1590/s1519-38292012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Triagem sorológica para doença celíaca em adolescentes e adultos jovens, estudantes universitários

Abstract: OBJETIVOS: avaliar a positividade sorológica para doença celíaca em um grupo de adolescentes e adultos jovens da cidade do Recife, Nordeste do Brasil. MÉTODOS: a amostra foi composta por estudantes matriculados nos cursos de graduação do Centro de Ciências da Saúde da Universidade Federal de Pernambuco. Os estudantes foram submetidos à coleta de sangue para pesquisa sorológica do anticorpo antitransglutaminase tecidual humana e responderam a questionário sobre sintomas e condições mórbidas associadas à doença … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
(42 reference statements)
0
2
0
2
Order By: Relevance
“…Population-based studies that discuss about the CD seroprevalence characterization in Brazil are rare. Data of studies performed in specific populations identified that the positivity prevalence of the anti-TtG antibody varied from 0.28 to 1.76% in adolescents and adults from the South, Southeast and Northeast areas 12,17,[19][20][21] . Seroprevalence through the anti-tTG IgA antibody of 3.80 22 , 3.37 4 and 4.56% 14 were seen in children and adolescents of Pernambuco, percentages that are expressively higher than that seen (0.49%) in adolescents from Salvador.…”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies that discuss about the CD seroprevalence characterization in Brazil are rare. Data of studies performed in specific populations identified that the positivity prevalence of the anti-TtG antibody varied from 0.28 to 1.76% in adolescents and adults from the South, Southeast and Northeast areas 12,17,[19][20][21] . Seroprevalence through the anti-tTG IgA antibody of 3.80 22 , 3.37 4 and 4.56% 14 were seen in children and adolescents of Pernambuco, percentages that are expressively higher than that seen (0.49%) in adolescents from Salvador.…”
Section: Discussionmentioning
confidence: 99%
“…Pernambuco (28) 2012 8 11.7 North east (African origins) (2) 2012 0 0 Mangueirinha (Kaingang & Guarani) (43) 2010 0 0…”
Section: Uk and Irelandmentioning
confidence: 99%
“…A modo de resumen de la bibliografía analizada, se podrían dividir a los pacientes en 2 grupos 16,19,35,40 , para luego definir la conducta a seguir.…”
Section: Recomendaciones Para El Diagnóstico De La Enfermedad Celíacaunclassified
“…Estos resultados podrían poner a elección del paciente si desea continuar con otros estudios serológicos, como el estudio genético (HLA DQ2/DQ8) o con biopsia 19,35 . Si se decide por los estudios de laboratorio, se recomienda medir los AAE, y si estos son positivos, puede diagnosticarse EC y comenzar la dieta sin gluten 19,21,30,35,40 En aquellos que fueron diagnosticados en este grupo, se implementa una DLG y se espera a la resolución de la sintomatología específica y normalización de los anticuerpos 20,25 . El 70 % de los pacientes tiene mejoría clínica en las primeras dos semanas de dieta 43 .…”
Section: Recomendaciones Para El Diagnóstico De La Enfermedad Celíacaunclassified